2017
DOI: 10.17221/9/2017-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of rapeseed and linseed oils to sheep rations: effects on ruminal fermentation characteristics and protozoal populations

Abstract: Majewska M.P., Miltko R., Bełżecki G., Skomiał J., Kowalik B. (2017): Supplementation of rapeseed and linseed oils to sheep rations: effects on ruminal fermentation characteristics and protozoal populations. Czech J. Anim. Sci., 62, 527−538.The study was performed on six sheep fitted with a cannula in the rumen and re-entrant cannula in the duodenum; divided into three groups, two sheep in each. The animals were fed meadow hay and the concentrate alone or the same diet supplemented with rapeseed or linseed oil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…Moreover, MSO with more than 70% unsaturated fatty acid contents, can be used as an effective tool to alter fatty acid profiles of milk and meat by reducing saturated and trans fatty acids while increasing unsaturated fatty acids. Results of supplementation of MSO on milk production observed in this study are in agreement with earlier studies which used fish oil (Whitlock et al, 2006;Heravi et al, 2007;and Barfourooshi et al, 2018), rapeseed and linseed oil (Majewska et al, 2017) as a fat supplements. Other studies have not reported any effect of fish oil on milk production.…”
Section: Effect Of Mso On Milk Yield and Composition Of Lactation Ewessupporting
confidence: 93%
“…Moreover, MSO with more than 70% unsaturated fatty acid contents, can be used as an effective tool to alter fatty acid profiles of milk and meat by reducing saturated and trans fatty acids while increasing unsaturated fatty acids. Results of supplementation of MSO on milk production observed in this study are in agreement with earlier studies which used fish oil (Whitlock et al, 2006;Heravi et al, 2007;and Barfourooshi et al, 2018), rapeseed and linseed oil (Majewska et al, 2017) as a fat supplements. Other studies have not reported any effect of fish oil on milk production.…”
Section: Effect Of Mso On Milk Yield and Composition Of Lactation Ewessupporting
confidence: 93%
“…Rumen fermentation characteristics are considered to be effective indicators in the evaluation of feeds and feeding for ruminants [1]. However, the once-or twice-daily feeding regime, which results in large fluctuations in rumen fermentation, as well as variable nutrient flows for utilization by ruminants, has often been employed in previous studies [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, it was shown that acetate, propionate and butyrate administered intravenously stimulated pancreatic juice flow. It was found that linseed oil addition to sheep diets significantly increased the concentration of VFAs in rumen fluid, particularly of acetate, in comparison with the control group (Majewska, Miltko, Bełżecki, Skomiał, & Kowalik, ). Harmon () reported that suckling ruminants without fully developed forestomach, receiving only milk, were more sensitive to diet modifications than adult ruminants.…”
Section: Ingredients and Chemical Composition Of The Diet For Sheepmentioning
confidence: 93%
“…() in which increased activity of lipase in cows fed different physical forms of rapeseed in comparison to control animals was observed. In our previous study, it was shown that the elevated activity of lipase appeared to be the result of the higher daily fat intake by the sheep and increased fat flow to the duodenum (Majewska, Miltko et al., ). Moreover, the present study demonstrated the increasing trend in the bile–pancreatic juice secretion associated with elevated lipase activity in sheep fed diets with oils addition.…”
Section: Ingredients and Chemical Composition Of The Diet For Sheepmentioning
confidence: 95%